(untitled) (Beacon: International Journal of Education and Social Studies, 2025)
This study aimed to explore teachers’ practices in implementing the Merdeka Curriculum in English classes at junior high schools in Bekasi City. A qualitative case study design was employed to gain an in-depth understanding of teachers’ experiences and instructional practices. The participants consisted of three English teachers from three junior high schools selected through purposive sampling based on their experience in implementing the Merdeka Curriculum. Data were collected through semi-structured interviews, classroom observations, and document analysis. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data condensation, data display, conclusion drawing, and verification. The findings revealed that teachers exercised considerable autonomy in designing instructional activities that accommodated students’ diverse needs and learning characteristics. Various student-centered teaching strategies, including Project-Based Learning, collaborative learning, and the Genre-Based Approach, were implemented to enhance student engagement and language learning outcomes. Technology integration was also utilized to support interactive learning experiences. In terms of assessment, teachers employed authentic assessment methods such as projects, presentations, portfolios, and peer assessment, reflecting the principles of the Merdeka Curriculum. However, several challenges remained, including limited time for developing differentiated instruction, diverse student abilities, and the need for continuous professional development. The study concludes that the implementation of the Merdeka Curriculum in English classrooms at junior high schools in Bekasi City has promoted more flexible, student-centered, and competency-based teaching practices while highlighting the importance of ongoing support for teachers.